3D flower-like ZnFe-ZIF derived hierarchical Fe, N-Codoped carbon architecture for enhanced oxygen reduction in both alkaline and acidic media, and zinc-air battery performance. (May 2020) - Zhang, Zhiwei; Jin, Huihui; Zhu, Jiawei; Li, Wenqiang; Zhang, Chengtian; Zhao, Jiahuan; Luo, Feng; Sun, Zhigang; Mu, Shichun
Abstract: Developing highly efficient and durable noble-metal-free electrocatalysts towards oxygen reduction reaction (ORR) is desperately urgent for realizing widespread application of fuel cells and metal-air batteries. Recently, great importance has been attached to metal-organic framework (MOF)-derived carbon-based materials due to the low cost and excellent performance. Herein, a novel zeolitic imidazole framework (ZnFe-ZIF) with a unique 3D flower-like morphology is synthesized in an aqueous solution, and then directly converted into Fe, N-codoped carbon frameworks with carbon nanotubes by a one-step pyrolysis process, which inherits the structure of the precursor. By virtue of advantageous structural features, sufficient active sites (especially efficient FeNx moieties), the as-obtained electrocatalyst possesses superior ORR performance in alkaline media with a half-wave potential of 0.89 V outperforming that of commercial Pt/C (0.84 V), and good approaching activity to Pt/C (0.78 V) in acidic media. In addition, it exhibits better stability and methanol/CO resistance than those of commercial Pt/C under both alkaline and acidic conditions. Moreover, the primary zinc-air battery using this electrocatalyst delivers a maximum power density of 131.7 mW cm −2, and a high specific capacity of 720 mAh g −1 and energy density of 880 Wh kg −1 at 20 mA cm −2 . Graphical abstract: A novel 3D flower-like ZnFe-ZIF derived hierarchical Fe, N-codoped carbon architecture is designed. The synthetic route is extremely simple, green, cost-effective and scalable. The prepared Fe–N-CNTs catalyst shows a superior ORR activity and stability in alkaline media, far better than commercial Pt/C, and comparable ORR activity to Pt/C in acidic media. Importantly, its practical application is demonstrated in actual Zn-air batteries with maximum power density of 132 mW cm −2, specific capacity of 720 mAh g −1 and energy density of 880 Wh kg −1 at 20 mA cm −2 . Image 1